3R, 3?R zeaxanthin Protects Retina from Photo-Oxidative Damage: in vivo model - Sahin, Nurhan; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Yilmaz, Ismet; Juturu, Vijaya (Wiley, 2017)
[Abstract Not Available]
Experimental Biology (EB) Annual Meeting -- APR 22-26, 2017 -- Chicago, IL